Determinants of Capital Structure: Evidence from Polish Food Manufacturing Industry - Jacek Jaworski; Leszek Czerwonka; Magdalena Madra-Sawicka (German Journal of Agricultural Economics (GJAE), 2019)
The aim of this paper is to identify factors influenc-ing the capital structure of Polish food manufacturing companies. In the first part of the paper, the most probable determinants of the capital structure have been identified on the basis of literature review and the current research conducted in this field. The second part of the paper presents an empirical verification of the relationship between capital structure and its fundamental determinants. The study was made using panel models. The scope of the survey covered Polish food companies between 2012 and 2015. Key determinants of total debt in the food manufacturing companies include: share of fixed assets in total assets, liquidity, profitability and non-debt tax shield with negative relationship. These factors also include: business size and growth with a positive relationship. For the long-term debt, the following factors are important: share of fixed assets in total assets, size of the business and liquidity (positive relationship). A negative relationship has been diagnosed for profitability and non-debt tax shield. The identified factors and the direction of dependence are similar to those previously diagnosed in the Czech Republic and Italy. However, they differ significantly from those of the US and Turkey. The capital structure of Polish food enterprises, measured by the total debt ratio, is best explained by the pecking order theory, while the share of long-term debt in the capital structure can be explained by static trade-off theory.
Keywords: 330